Innovation or imitation: A patent race approach - Kaynarca, Nurten (My University, 2019)
Innovation and imitation of technology are intensively discussed in the literature of economic development. In spite of many empirical and theoretical findings revealing the importance of innovation for rapid economic development, the developing economies are still behind developed economies in terms of R&D expenditure and its share in GDP. Hence, the reason behind differential levels of development among countries cannot be just be the limited resources in the lagging countries as compared to developed countries. Therefore, understanding the motivation of firms to make R&D expenditure for innovation is crucial. Patent race models are important contributions to the literature in this direction. Patent races are multi agent-based models that discusse the R&D investments of firms to obtain patent protection for a specific technology. In our model, we pursue a patent race approach to the technological gap between incumbent and entrant firms as well as innovation and imitation decisions of entrant firms. The return of successful innovation and the probability of early success are differentiated for incumbent and entrant firms. The model is calibrated by the mobile phone sector data. The calibration suggests that there is a subtantial gap between the probabilities of early success of incumbents and entrants and. Moreover, staying out of patent races (imitation) is more profitable for an entrant firm at the calibrated parameter levels.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Market structure; Patent race; Innovation; Imitation; Piyasa yapısı; Patent yarışları; İnovasyon; İmitasyon